MDM2 inhibitors-mediated disruption of mitochondrial metabolism: A novel therapeutic strategy for retinoblastoma - Romani, Arianna; Zauli, Enrico; Zauli, Giorgio; AlMesfer, Saleh; Al-Swailem, Samar; Voltan, Rebecca (Frontiers in Oncology, 2022)
MDM2 is the principal inhibitor of p53, and MDM2 inhibitors can disrupt the physical interaction between MDM2 and p53. The half-life of p53 is very short in normal cells and tissues, and an uncontrolled increase in p53 levels has potential harmful effects. It has been shown that p53 is frequently mutated in most cancers; however, p53 mutations are rare in retinoblastoma. Therefore, therapeutic strategies aimed at increasing the expression levels of wild-type p53 are attractive. In this minireview, we discuss the potential use of nutlin-3, the prototype small molecule inhibitor that disrupts the MDM2-p53 interaction, for the treatment of retinoblastoma. Although p53 has pleiotropic biological effects, the functions of p53 depend on its sub-cellular localization. In the nucleus, p53 induces the transcription of a vast array of genes, while in mitochondria, p53 regulates mitochondrial metabolism. This review also discusses the relative contribution of p53-mediated gene transcription and mitochondrial perturbation for retinoblastoma treatment.